Influence of physical preconditioning on the responsiveness of rat pulmonary artery after pulmonary ischemia/reperfusion - Delbin, Maria Andréia [UNESP]; Moraes, Camila [UNESP]; Camargo, Enilton; Mussi, Ricardo K.; Antunes, Edson; de Nucci, Gilberto; Zanesco, Angelina [UNESP] (Elsevier, 2007)
The aim of this work was to evaluate the effect of physical preconditioning in the responsiveness of rat pulmonary rings submitted to lung ischemia/reperfusion (IR). Wistar rats were divided into three groups: Sedentary sham-operated (SD/SHAM); sedentary submitted to ischemia/reperfusion (SD/IR) and trained submitted to ischemia/reperfusion (TR/IR) animals. Exercise training consisted in sessions of 60 min/day running sessions, 5 days/week for 8 weeks. Left pulmonary IR was performed by occluding for 90 min and reperfusing for 120 min. After that, pulmonary arteries were isolated and concentration-response curves to acetylcholine (ACh), histamine (HIST), sodium nitroprusside (SNP), phenylephrine and U46619 were obtained. Neither potency (- log EC50) nor maximal responses (Emax) were modified for ACh and HIST in all groups. On the other hand, the potency for SNP was significantly increased in TR/IR group (8.23 ± 0.06) compared to SD/IR group (7.85 ± 0.04). Contractile responses mediated by a-adrenergic receptor were markedly decreased in IR groups (SD/IR: 6.75 ± 0.06 and TR/IR: 6.62 ± 0.04) compared to SD/SHAM (7.33 ± 0.05). No changes were seen for the U46619 in all groups. In conclusion, the present study shows that exercise training has no protective actions in the local blood vessel where the IR process takes place. © 2006 Elsevier Inc. All rights reserved.
Keywords: Contractile responses; Exercise training; Pulmonary artery ring; Pulmonary ischemia/reperfusion; Relaxation response; 15 hydroxy 11alpha,9alpha epoxymethanoprosta 5,13 dienoic acid; acetylcholine; alpha adrenergic receptor; histamine; nitroprusside sodium; phenylephrine; animal experiment; animal model; animal tissue; blood vessel; concentration response; controlled study; drug mechanism; exercise; ischemia; male; nonhuman; protection; pulmonary artery; rat; reperfusion; respiratory system; running; sitting; therapy effect; Animals; Blood Pressure; Body Weight; Dose-Response Relationship, Drug; Lung; Nitrates; Nitrites; Physical Conditioning, Animal; Pulmonary Artery; Rats; Rats, Wistar; Reperfusion Injury; Vasoconstrictor Agents; Vasodilator Agents; Animalia; Rattus; Rattus norvegicus